Flora of Gayo Plateau II: Corybas gayoensis (Orchidaceae), a new narrow endemic orchid from Sumatra - Mustaqim, Wendy A.; Arico, Zulfan; Silviana, Adinda; Afriyani, Linda; Yudistira, Yuda R.; Victoriano, Malcolm (Phytotaxa, 2025)
A new species, Corybas gayoensis is described here as endemic to the northern part of Sumatra. The new species is similar to Corybas pictus, but differs in having acuminate dorsal sepals with dentate upper margin, labellum with light red and concave central part, and a long fimbriate margin. The species is assessed as Critically Endangered due to its narrow distribution, continuous decline of population and habitat degradation. Detailed descriptions, illustrations, photographs, and discussion are given.